Slovene language from word to sign. An example of the use of the Slovene Sign Language in school - Kerman De Luisa, Ana Elizabeta; Žele, Andreja (Revija za elementarno izobraževanje, 2023)
Both language systems, spoken Slovene and Slovene Sign Language, are composed of basic word formation or sign formation elements, which act as cornerstones for compounded words and signs. The formation of new words in Slovene language is realised by adding suffixes after the base or stem of a word, linking together two or more bases with infixes, or adding prefixes before the base or stem of a word. To express these word formation types, sign formation adopts visual elements: facial expression, hand- and finger shape, signing speed, signing orientation and signing space.
Keywords: Slovene language, Slovene sign language, basic and compounded sign, interpreting, teaching.